Knyga masinės komunikacijos priemonių sistemoje - Samėnas, Alvydas (Knygotyra, 1972)
In the present article an attempt has been made to determine the place of the book and its relations with other communication means in the system of mass communication. Since the book can serve as a channel of mass and scientific communication it has been attempted here to analize it in the first aspect.The results of the sociological investigations of communications carried out in the USSR and other socialist countries show that the book is means of medium popularity of mass communication, although this does not diminish its importance.In the modern society none of the means of mass communication can occupy an exclusive position both because of its technical possibilities being limited and of the fact that the man himself is inclined to use the whole system of communications.